الإعلام الجديد والمشاركة الانتخابية في الجزائر - طالب حفيضة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهتم هذه الدراسة بفهم تأثير الإعلام الجديد على المشاركة الانتخابية في الجزائر، لاسيما وأنّ الأحداث التي شهدتها الجزائر في السنوات القليلة الماضية، أبانت عن دور وسائل التواصل الاجتماعي في تعبئة الناخبين، من خلال حثهم على مقاطعة الانتخابات لإظهار عدم شرعية النظام السياسي. وعليه سنحاول من خلال هذه المداخلة التطرق إلى كيفية استغلال منابر الإعلام الجديد لحشد تأييد الرأي العام. Abstract: This study is concerned with understanding the impact of the new media on the electoral participation in Algeria, especially since the events that Algeria witnessed in the past few years, demonstrated the role of social media in mobilizing voters, by urging them to boycott the elections, to show the political regime’s lack of legitimacy. Therefore, we will try through this study to address how to use the new media platforms to mobilize public opinion.